The school age child with autism/autism spectrum disorders (ASD) - Le Couteur, Ann (Henry Stewart Talks, 2010)
Overview of current understanding of the needs of school aged children with autism/autism spectrum disorders, Definitions and prevalence of autism/ ASD, Multidisciplinary multiagency assessment for a child with a suspected ASD using the model of the UK National Autism Plan for children, Child and family based interventions, The importance of recognizing co-morbid and co-occurring conditions, Challenges for current clinical and research practice